Чисельний аналіз магнітного поля циліндричного трифазного індуктора магнітного сепаратора - Мілих, Володимир Іванович; Шилкова, Лариса Василівна; Ревуженко, Світлана Афанасіївна (НТУ "ХПІ", 2017)
Наведено електромагнітну систему індуктора магнітного сепаратора, яку побудовано на основі статора трифазного асинхронного двигуна. Сформовано квазі-тривимірну математичну модель і викладено принцип розрахунку магнітного поля в об'ємі індуктора. Це засновано на методі плоско-ортогональних розрахункових моделей, що поєднують магнітні поля поперечного та поздовжнього перерізів індуктора. Сформовано комплекс граничних умов, що забезпечує адекватну структуру магнітного поля в робочій зонііндуктора. За допомогою програми FEMM виконано розрахунковий аналіз магнітного поля в двох перерізах індуктора.

The electromagnetic system of the magnetic separator inductor is presented. Its design is based on a three-phase induction motor stator. A quasi-three-dimensional mathematical model describing the magnetic field of the inductor is formed, and a methodfor calculating this field in its volume is set out. The basis of this is the method of plane-parallel design models, that combines the transverse and longitudinal sections of the inductor. The magnetic fields of these sections are connected on the central radial line, which is common for them. These magnetic fields are described by differential equations through the vector magnetic potential, for which a complex of boundary conditions is formed. They provide an adequate structure of the magnetic field in the inductor working area. A calculated analysis of the magnetic field in two sections of the inductor is carried out on the presented theoretical basis In this case, the role of two factors ensuring the magnetic field excitation in its complete design model is revealed. Calculations of magnetic fields in each section are carried out by the finite element method of FEMM program. It is shown that a practically uniform distribution of the magnetic induction of the inductor field is provided in the cross section of theinductor working zone. A magnetic field gradient (which helps) helping to retain in it the ferromagnetic elements that are the tool of the separator working process is obtained in the longitudinal section at the boundary of this zone.
Numerical analysis of the magnetic field of a cylindrical three-phase magnetic separator inductor
Keywords: математична модель; поперечний переріз; поздовжній переріз; граничні умови; розрахунковий аналіз; magnetic separator; inductor; magnetic field; mathematical model; transverse section; longitudinal section; boundary conditions; computational analysis